Estado actual socio económico y tecnológico de la industria del aserrío de madera en la Provincia de Maynas – Loreto – Perú 2023 - López Pérez, James (2024)
The research work was carried out in sawmill companies in the city of Iquitos, in the province of Maynas, with the objective of evaluating the current state of the wood sawmill industry, based on the social, economic and technological diagnosis. The results obtained show that: The plant personnel is the one with the largest population with 456 workers totaling 55% of the total. The social and economic level of the personnel working in the wood industry in the Loreto region, according to what you mention, presents a clear differentiation between workers (Level D and E) and employees or officials. This situation reflects the hierarchical structure and division of labor within the industry. The plant personnel required for the sawmilling process is 18 people. Metropolitan Iquitos has 26 sawmills in operation, of which 7 (27%) are in the district of San Juan, 14 (54%) in the district of Punchana, 2 (8%) in the district of Belén and 3 (12%) in the district of Iquitos. 42% of the sawmills are located in the district of San Juan, 14 (54%) in the district of Punchana, 2 (8%) in the district of Belén and 3 (12%) in the district of Iquitos. Forty-two percent of the sawmills have machinery that is between 21 and 30 years old. This indicates that a considerable part of the equipment used is near the end of its useful life; 27% of the sawmills have machinery that is more than 30 years old, which suggests that maintenance can be costly. According to their classification, there is commercial longwood, commercial longwood, narrow longwood, shortwood and planks, and quarters.